Proposed new interior design scheme for Pit Stop Camera Sdn Bhd of Canon at S1, Level 2 USJ 19 Subang Jaya Selangor Darul Ehsan / Muhammad Nafis Ridzuan - Ridzuan, Muhammad Nafis (Faculty of Architecture, Planning and Surveying, 2010)
The final project for the student of Diploma in Interior Architecture is a manifestation towards the student’s knowledge about the whole aspect on interior design that had been learnt from basic to the final presentation on the proposed design. The project that had been chosen for the final project is to propose New Scheme Design Of Pit Stop Centre Camera for Canon Sdn Bhd. This proposed Pit Stop Centre Camera is to attract users, especially all the Canopn users from any race to try for all the latest new products.. The target customer are mostly from government staff, VIP person, family.Concept and image that had been chosen not only must be suitable with the clients as both of it would reflect the client itself, but at the same time it would give a positive impact and to increase the business.Besides, the concept and images itself should be also related with the theme of the Pit Stop Centre Camera. Some of the gained information of the study is through interviews, printed media, internet, observation, and through the result from the case study either locally or internationally.